Outstanding administrators must prepare to improve knowledge and competency - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 22 June 2021 - The role of university administrators is to carry out excellent duties and always use their minds to gain knowledge and enhance competencies.